Re-signification of H. E. Adıvar’s Novel “The New Turan” - Şahin, Veysel (Atatürk Kültür Merkezi Başkanlığı, 2013)
Halide Edip Adıvar searches for remedies for the salvation and the re-establishment of the Turkish nation in her novel ‘The New Turan’ . Therefore, the author deals with the issues of the country as well as her individual senses and ideas. Adıvar, turning from individualism to the national in that novel, puts forward new ideas fort he establish ment and salvation of the nation by dealing with the themes such as the ideal love and national conscious as well as social anielanation , degeneration, and the educational and health problems. Thus, the au thor puts the struggle for existence of the Turkish nation on the paper

Halide Edip Adıvar, ‘Yeni Turan’ romanında Türk milletinin yeniden ku ruluş ve kurtuluşu için çareler arar. Bu nedenle yazar, bireysel duygu ve fikirlerinin yanında memleketin sorunlarını da işler. Bu romanında, bireysellikten millî olana yönelen Adıvar, yabancılaşma, yozlaşma, eğitim ve sağlık problemlerinin yanında maksat aşkı, millî benlik, gibi izlekleri ele alarak ülkenin yeniden kuruluş ve kurtuluşu için yeni fikir ler ortaya koyar. Böylece yazar, Türk milletinin varoluş mücadelesini bütün yönleriyle metinleştirir.
Halide Edip Adıvar’ın ‘Yeni Turan’ Romanını Yeniden Anlam(landırm)a